(untitled) (Research, Society and Development, 2023)
Objective: to determine the incidence of fungal infections in patients with Covid, to determine the main topographies and the outcome of patients admitted to an Intensive Care Unit (ICU) of a university hospital in the brazilian Northeast. Methodology: This is a cross-sectional, quantitative study, carried out in the ICU of a university hospital in the brazilian Northeast, from May 2020 to December 2021. Results: Of 252 patients admitted to the COVID ICU, 126 (50,4%) were male and 124 (49,6%) were female. The age group with the highest incidence of nosocomial infections associated with Covid occurred in patients over 60 years of age. As for topography, 74 (29,4%) patients had ventilator-associated pneumonia, 63 (25%) pyogenic primary bloodstream infection, 53 (21%) laboratory ventilator-associated pneumonia, and 44 (17,5%) respiratory tract infections urinary. 70 (38,9%) of the infections were diagnosed through peripheral blood culture and 54 (30%) through tracheal aspirate. Of the total infections, 30 (11,9%) were caused by candida albicans and 23 (9,1%) by non-albicans candida. There were 138 (54,8%) deaths, 23 (62,2%) caused by candida albicans and 14 (37,8%) by non-albicans candida. Conclusion: This study highlights the importance of preventive measures as indicated by patient safety protocols, and of Constant updates for health professionals regarding the proper management of patients in hospital care.